Analisis pengaruh variable makroekonomi terhadap pengangguran di negara ASEAN - Sukmawati, Diyah Ari (Economics, Finance, and Business Review, 2025)
This study aims to analyze the factors that influence the unemployment rate in ASEAN countries. This study takes a case study in 9 ASEAN countries during the period 2013 to 2019. The analysis tool used is panel data regression with the best model, namely fixed effect. The results of the study show that macroeconomic variables, namely inflation and exchange rates, have a positive effect on the unemployment rate in ASEAN countries. On the other hand, the GDP variable has a negative effect, meaning that the higher the GDP, the lower the unemployment rate. The test results show that the FDI and export variables do not have a significant effect on the unemployment rate. The implication of this study is the importance of controlling macroeconomic variables to overcome unemployment rates in ASEAN countries. The variable that has the greatest impact on unemployment in ASEAN countries is inflation with a coefficient value of 0.0403. The results of this study imply that the government needs to control and maintain conducive macroeconomic variables through accommodative monetary and fiscal policies to reduce the unemployment rate.